Linguistic analysis of large corpora: approaches to computational linguistics in Hungary. - Hunyadi, L (Literary & Linguistic Computing, 1999)
The paper is a summary of current computational linguistic research in Hungary aimed at the analysis of a large corpora. The pioneering work in the 1950s and 1960s by Ferenc Papp, the reverse alphabetized Dictionary of the Hungarian Language, laid the foundations of a tradition of analysing large textual corpora. Along this path, current work on the Historical Dictionary of Hungarian by J. Pajzs and F. Papp uses statistical approaches for morphological disambiguation. In a comprehensive work by T. Váradi, a large corpus of spoken Hungarian is precessed by methods of computational linguistics. The paper also discusses linguistic approaches to two programming languages: B. Hollósy employs FoxPro in educational and academic settings for the presentation and analysis of large amounts of linguistic data, and G. Alberti uses a PROLOG implementation to represent and verify a linguistic theory of minimal syntax and maximal lexicon.